Multiple One-Way Edge Modes in Sonic Crystals With Large Chern Numbers - Zhao, Han; Zhang, Tian; Zhang, Xiujuan; Lu, Ming-Hui; Chen, Yan-Feng (Frontiers in Physics, 2022)
The quantum Hall effect (QHE) associated with Chern insulators reveals the non-trivial topological properties of two-dimensional electronic systems subject to strong magnetic field, which features finite Chern number C and chiral edge states. The latter promise robust electron transport and have received tremendous attention in both the condensed matter physics and classical systems including photonics and acoustics. In acoustics, circulating airflow has been introduced to create an effective gauge magnetic field, which breaks the time-reversal symmetry and leads to chiral edge states for acoustic waves. While the robust edge states may offer possible routes towards acoustic devices yielding unidirectional sound propagation, e.g., acoustic diodes, the mode density at the interfaces is limited by small Chern numbers of ±1. Here, we realize acoustic Chern insulators with large Chern numbers, i.e., |C|≥1 (|C|=1, 2, 3, 4). The system is based on circulating airflow in a sonic crystal (SC) with fourfold rotational symmetry. The large Chern numbers are obtained by breaking multiple accidental degeneracies at (non-)high-symmetric points. Based on these Chern insulators, acoustic diodes are realized by joining structures of different Chern numbers. Up to 8 propagation modes are supported on the interfaces, greatly improving the mode density and hence the propagation efficiency. Our design offers possible routes towards high-efficient and topologically robust acoustic diodes, which may further inspire acoustic non-reciprocal devices based on topological Chern insulators. Experimentally, our proposals can be realized based on angular-momentum-biased resonator arrays.